ØªØ£Ø«ÙŠØ± Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¥Ø¹Ø²ÙŠØ© ÙÙŠ ØªØ±Ù‚ÙŠÙ‡ Ø¹Ø¯Ø¯ ØÙØ¸ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Siti Laili Agustina; Ruwaida Hudatullah (Lughatu Ad-dhat, 2021)
One of the problems that often occur in schools, including the secondary school for female teachers, Nahdat al-Watan, and publishing in Arabic language learning, is that students do not memorize Arabic vocabulary. Because of the problems mentioned above, the author decided to conduct research with the formulation of the problem. Vocabulary of the Arabic language for tenth grade students in the secondary school teachers Nahdhat Al-Watan Finchour The destination is to find out whether the condolence method has an effect on achieving memorizing Arabic vocabulary for the ten semester of the Secondary School Teachers Nahdet Al-Watan, for publication. The design used in this study is an experimental model from One Group Pretest PosttestDesign. Based on the results of the hypothesis test analysis, the significance value (p): 0,26 was obtained. That is, if the significance value is less than 0.05, then the significant alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Based on testing the hypotheses, it can be concluded that the use of the method of Al-Moazzi is an effect in the investigation of preserving the Arabic language vocabulary for the ten semester of the secondary school teachers Nahdhat Al-Watan Finchour.